(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Following ratification of the United Nations (UN) Convention on the Elimination of All Forms of Discrimination Against Women, the Japanese government enacted the Law Respecting the Improvement of the Welfare of Women Workers, Including the Guarantee of Equal Opportunity and Treatment Between Men and Women in Employment (the Equal Opportunity Act) in 1985 and spent the next twenty-five years enforcing it. As a result, political obstacles to workplace gender equality are slowly but gradually disappearing in Japan. However, in addition to political constraints, social and structural barriers inside firms also remain. The elimination of these extra barriers is important if we are to develop a society where truly egalitarian employment can be accomplished. It is possible to see some improvements in these cultural barriers in contemporary Japanese society as a result of changes in the functions of a college degree and changes in the family techniques that couples pick based on their financial situations. Employees’ ability to advance in the workplace today, under the lifetime employment system, may be a result of their participation in the competitive promotion process, independent of gender. College-educated women may still feel significant hurdles, although they are getting thinner under the leadership of the national government.